2023
DOI: 10.1021/jacs.3c01682
|View full text |Cite
|
Sign up to set email alerts
|

meso-Methyl BODIPY Photocages: Mechanisms, Photochemical Properties, and Applications

Abstract: meso-methyl BODIPY photocages have recently emerged as an exciting new class of photoremovable protecting groups (PPGs) that release leaving groups upon absorption of visible to near-infrared light. In this Perspective, we summarize the development of these PPGs and highlight their critical photochemical properties and applications. We discuss the absorption properties of the BODIPY PPGs, structure−photoreactivity studies, insights into the photoreaction mechanism, the scope of functional groups that can be ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 139 publications
1
14
0
Order By: Relevance
“…, halides and acetate). 37 The nomenclature adopted herein is BODIPY-Z-X-R , where Z is F or Me , X is H or Br , and R is the meso -methyl cargo ( e.g. , TMG ).…”
Section: Resultsmentioning
confidence: 99%
“…, halides and acetate). 37 The nomenclature adopted herein is BODIPY-Z-X-R , where Z is F or Me , X is H or Br , and R is the meso -methyl cargo ( e.g. , TMG ).…”
Section: Resultsmentioning
confidence: 99%
“…A relatively recent but extensively studied addition to the field of PPGs is boron-dipyrromethene (BODIPY)-based PPGs, which have shown to be biocompatible, easily tuneable, and highly selective in their photocleavage range. 14–21 Additionally, they can cleave in optical ranges that are less harmful to living cells, such as the green and red-light regions. Further, BODIPY PPGs can be used to cap a wide range of cargo, including primary amines, such as dopamine and histamine, and carboxylic acids, such as nitrophenylacetic acid.…”
mentioning
confidence: 99%
“…Further, recent studies have demonstrated that while photocleavage of similarly-structured BODIPY-based PPGs in air and aerated solutions results in a reduced quantum yield, photocleavage still proceeds. 19,20…”
mentioning
confidence: 99%
“…14 Furthermore, they have been used as efficient photosensitizers, 15,16 photocatalysts 17,18 and photocages. [19][20][21][22][23][24] BODIPYs are also considered as potential candidates for circularly polarized luminescence. 25 Classically, dyes of the BODIPY family are built up by formation of a dipyrromethene through condensation and oxidation chemistry followed by the insertion of the chelating BF 2 unit via BF 3 ÁOEt 2 .…”
mentioning
confidence: 99%